Hydrology of a Constructed Fen Watershed in a Post-mined Landscape in the Athabasca Oil Sands Region, Alberta, Canada - Ketcheson, Scott (University of Waterloo, 2015)
Peatlands (i.e., wetlands with organic soil) cover approximately 12% of Canada’s total land area, 18% of Alberta’s land base and nearly half of the landscape in Canada’s Western Boreal Plain. Some of these peatlands overlay vast fossil fuel resources. Mounting pressure from resource extraction industries is impacting an increasing proportion of peatland ecosystems in Canada. In Alberta, approximately 4800 km2 of the Athabasca Oil Sands Region near Fort McMurray has been deemed suitable for surface mining, which involves the removal of large expanses of undisturbed peatlands to access the oil sands beneath. The concept of peatland creation has been adapted into the Canadian regulatory framework and fen peatlands have now been constructed in post-mined oil sands landscapes. However, there is little information with respect to the nature of the hydrological processes that operate within constructed fen ecosystems and their associated watersheds and this concept is only now being tested in the field. Oil sands reclamation requires the reconstruction of entire landforms and drainage systems. The hydrological regime of reclaimed landscapes will be a manifestation of the processes operating within the individual landforms that comprise it. Hydrology is the most important process regulating wetland function and development, as it exhibits a strong control on the chemical and biotic processes operating in peatlands. Accordingly, this research aims to tackle the growing and immediate need to understand the hydrological processes that operate within reconstructed landscapes. The approach is to couple the controls on water distribution, storage and release within several reclaimed landforms (reclaimed slopes, tailings sand upland aquifer and fen peatland) to the function of a constructed fen watershed (the Nikanotee Fen watershed). A comparison of two constructed fen ecosystems with fundamentally different conceptual approaches provides the framework for examination of the key challenges and opportunities associated with ...